Unpaid family caregiving responsibilities, employee job tasks and work‐family conflict: A cross‐cultural study. (8th December 2020) - Bainbridge, Hugh T. J.; Palm, Esther; Fong, Man Mandy
Abstract: Employment is often undertaken simultaneous with providing unpaid care for an elderly or disabled family member. These dual responsibilities can create substantial inter‐role conflict. The current study considers how these roles affect work‐family conflict by examining: (i) the process which the gender of employees with caregiving responsibilities shapes work‐family conflict and (ii) whether this effect of employee gender is moderated by the societal level of gender egalitarianism. Data were collected from employees with caregiving responsibilities in 33 European countries. Findings suggest that the mediated relationship between gender and work‐family conflict is moderated by gender egalitarianism. As gender egalitarianism increases, women's commitment to caregiving is unchanged, while men, contrary to expectations, provide less caregiving. This gendered effect leads to an adjustment in an employee's job tasks, which in turn, reduces work‐family conflict. Overall, the findings suggest that gender, job tasks and cross‐cultural variables are important considerations at the interface of employment and caregiving.